Pengaruh Variasi Konsentrasi Inhibitor dari Kitosan Sisik Ikan terhadap Perilaku Korosi Besi ASTM A36: Studi Ekstrapolarisasi Tafel dan EIS - Hidayatullah, Syarif; Gapsari, Femiana; Setyarini, Putu Hadi (Jurnal Rekayasa Mesin, 2020)
Corrosion is the deterioration of metal that can reduce its yield strength, ultimate strength, financial losses, waste of natural resources, and endanger security. Thus, the corrosion rate must be slowed, or if possible, stopped. This study aimed to investigate the mechanism of corrosion protection by using corrosion inhibitors of chitosan extracted from fish scales on ASTM A36 steel. ASTM A36 steel was used as the specimen with a thickness of 3 mm. Fish scales powder was used as chitosan source extracted by using three mechanisms, i.e., deproteination (7% NaOH immersion), demineralization (immersion of 1 M HCl in 100 ml) and deacetylation (immersion process with 70% NaOH concentration). Corrosion inhibitor was composed of 8 g of chitosan from fish scales, 50 ml of distilled water, and 1 ml of CH3COOH. Corrosion protection with the inhibition method was applied with variations in the inhibitor concentration (1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm, and 6000 ppm). The corrosion rate was tested by the polarization method and Electrochemical Impedance Spectroscopy (EIS). The result demonstrated that the effectiveness of corrosion protection started to increaseÂ from the concentration of 1000 ppm, 2000 ppm, 3000 ppm to 4000 ppm, with an effective value of 46.444%, 56.386%, 59.691%, and 72.630%, respectively. However, the effectiveness level started to decline from the concentrations of 5000 ppm to 6000 ppm, with 67.388% and 59.276%, respectively. This phenomenon occursÂ due to the inhibitor concentration has exceeded the maximum limit, so the interaction between inhibitor molecules was higher than the interaction between the inhibitor and the metal surface.